The genetics of clinical outcome in multiple sclerosis. - Ramagopalan, S; Deluca, G; Degenhardt, A; Ebers, G (2008)
Multiple sclerosis (MS) is a common inflammatory disease of the central nervous system (CNS), the clinical course of which varies considerably between patients. Genetic complexity and interactions with as yet unknown environmental factors have hindered researchers from fully elucidating the aetiology of the disease. In addition to influencing disease susceptibility, epidemiological evidence suggests that genetic factors may affect phenotypic expression of the disease. Genes that affect clinical outcome may be more effective therapeutic targets than those which determine susceptibility. We present in this review a comprehensive survey of the genes (both MHC- and non-MHC-related) that have been investigated for their role in disease outcome in MS. Recent studies implicating the role of the genotype and epistatic interactions in the MHC in determining outcome are highlighted.